The impact of high-velocity sand columns against rigid and deformable structures based on the smoothed particle hydrodynamics method. (1st April 2021) - Salehizadeh, A.M.; Shafiei, A.R.
Highlights: The high velocity soil-solid interaction is modeled base on two regimes of behavior A novel 2D algorithm based on the SPH method is proposed for soil-solid interaction Using FCSPH approach to model high-velocity soil slug impact on targets The rate-dependent plastic TLSPH approach is applied to simulate structure Impact of a sand slug on beam and rigid target is conducted against other studies. Abstract: The response of a structure subjected to the impact of a dry sand slug has been studied using a fully coupled approach, in which a novel algorithm based on the smoothed particle hydrodynamics (SPH) method is proposed for soil-solid interaction (SSI). The proposed algorithm is a hybrid continuum/discrete approach that can determine two regimes of contact behavior. When the granular assembly has a high relative velocity in dealing with the structure, initially, the short-term particle-to-particle contacts take place, resembling molecular collisions in a fluid and referred to as regime I. Then, the increase of the relative density of aggregate particles leads to semi-permanent contacts, referred to as regime II. The present aim is development of a coupling model that includes both regimes. The simulation of impact of granular slug into a rigid or deformable target leads to large numerical errors and even divergences. To overcome the limitation of traditional SPH approach that the density estimate is a major challenge in high-rate deformation problems, the number-density scheme is extended to the fully compressible approach. Finally, the proposed SSI Algorithm is validated with Liu et al.'s results [1] to simulate the interaction of a structure with sand slugs traveling at high velocities.